Association of strong risk of hTERT gene polymorphic variants to malignant glioma and its prognostic implications with respect to different histological types and survival of glioma cases. (28th August 2020) - Pandith, Arshad A.; Wani, Zahoor A.; Qasim, Iqbal; Afroze, Dil; Manzoor, Usma; Amin, Ina; Baba, Shahid M.; Koul, Aabid; Anwar, Iqra; Mohammad, Fozia; Bhat, Abdul R.; Shah, Parveen
Abstract: Background: Germline genetic variants of human telomerase reverse transcriptase ( hTERT ) are known to predispose for various malignancies, including glioma. The present study investigated genetic variation of hTERT T/G (rs2736100) and hTERT G/A (rs2736098) with respect to glioma risk. Methods: Confirmed cases ( n = 106) were tested against 210 cancer‐free healthy controls by the polymerase chain reaction‐restriction fragment length polymorphism technique for genotyping. Results: Homozygous variant 'GG' genotype of rs2736100 frequency was > 4‐fold significantly different in cases versus controls (39.6% 17.2%; p < 0.0001). Furthermore, variant 'G' allele was found to be significantly associated with cases (0.5 versus 0.2 in controls; p < 0.0001). Homozygous variant rs2736098 'AA' genotype (35.8% versus 23.8%) and allele 'A' (0.49 versus 0.34) showed a marked significant difference in cases and controls, respectively ( p < 0.05). In hTERT rs2736100, the GG genotype significantly presented more in higher grades and GBM ( p < 0.0001). Furthermore, the GG variant of hTERT rs2736100 had a poor probability with respect to the overall survival of patients compared to TG and TT genotypes (log rank p = 0.03). Interestingly, two haplotypes of hTERT rs2736100/rs2736098 were identified as GG and GA that conferred a > 3‐ and 5‐fold risk to glioma patients respectively, where variant G/A haplotype was observed to have the highest impact with respect to glioma risk ( p < 0.0001). Conclusions: The results of the present study indicate that hTERT rs2736098 and rs2736100 variants play an important role in conferring a strong risk of developing glioma. Furthermore, hTERT rs2736100 GG variant appears to play a role in the bad prognosis of glioma patients. Haplotypes GG and GA could prove to be vital tools for monitoring risk in glioma patients. Abstract : Germline variants of hTERT gene are known to confer risk to develop various malignancies, including glioma. hTERT rs2736100 'GG' significantly differed in cases versus controls (39.6% 17.2%; p < 0.0001/G allele (0.5 versus 0.2 in controls, p < 0.0001). GG significantly presented more in higher grades/GBM ( p < 0.0001). hTERT variant rs2736098 'AA' genotype (35.8% versus 23.8%) and allele 'A' (0.49 versus 0.34) showed significant difference in cases and controls ( p < 0.05). GG variant of hTERT rs2736100 had poor probability in overall survival of patients (log rank p = 0.03). Haplotypes GG and GA conferred a > 3‐ and 5‐fold risk to glioma patients respectively ( p < 0.0001). Thus, the present study concludes that these variants confer a strong risk of developing glioma and the rs2736100 GG genotype is implicated in the bad prognosis of glioma patients. Furthermore, GG and GA haplotypes could prove to be vital tools for monitoring glioma risk.